New Neurons in the Post-ischemic and Injured Brain: Migrating or Resident? - Nemirovich-Danchenko, Nikolai M.; Khodanovich, Marina Yu. (Frontiers in Neuroscience, 2019)
The endogenous potential of adult neurogenesis is of particular interest for the development of new strategies for recovery after stroke and traumatic brain injury. These pathological conditions affect endogenous neurogenesis in two aspects. On the one hand, injury usually initiates the migration of neuronal precursors (NPCs) to the lesion area from the already existing, in physiological conditions, neurogenic niche – the ventricular-subventricular zone (V-SVZ) near the lateral ventricles. On the other hand, recent studies have convincingly demonstrated the local generation of new neurons near lesion areas in different brain locations. The striatum, cortex, and hippocampal CA1 region are considered to be locations of such new neurogenic zones in the damaged brain. This review focuses on the relative contribution of two types of NPCs of different origin, resident population in new neurogenic zones and cells migrating from the lateral ventricles, to post-stroke or post-traumatic enhancement of neurogenesis. The migratory pathways of NPCs have also been considered. In addition, the review highlights the advantages and limitations of different methodological approaches to the definition of NPC location and tracking of new neurons. In general, we suggest that despite the considerable number of studies, we still lack a comprehensive understanding of neurogenesis in the damaged brain. We believe that the advancement of methods for in vivo visualization and longitudinal observation of neurogenesis in the brain could fundamentally change the current situation in this field.